The euro and corporate financing - Arturo Bris; Yrjö Koskinen; Mattias Nilsson (Bank of Finland, 2011)
In this paper we study how the introduction of the euro has affected corporate financing in Europe. We use firm-level data from eleven euro area countries as well as from a control group of five other European countries spanning the years 1991 2006. We show that firms from euro area countries that previously had weak currencies have increased both their equity and their debt financing compared to the control group. We also show that results are stronger for firms that hail from less financially developed euro area countries, and that large firms from industries that are dependent on external financing have increased their debt financing more. These results support the hypothesis that improved access to capital markets in the euro area has enabled increased external financing, especially debt financing.
URN:NBN:fi:bof-20140807274
Keywords: 330